Sino-American Rivalry: Global Climate Governance Leadership? - Yahya, Glory Yolanda; Gunawan, Desri; Permata, Inda Mustika; Nanda, Bima Jon (Andalas Journal of International Studies (AJIS), 2022)
This paper attempts to describe the competitive implications of the United States and China in global climate governance. It is important to discuss because China and the United States have been in intense competition in recent years. Besides, the United States decided to leave the Paris Agreement to provide space for China to become a leader in the government and strengthen its influence in the international world. China's active role certainly has implications for its competition with the United States. This paper uses qualitative methods with secondary data sources. The findings of this paper are that China's influence and commitment to the Paris Agreement show that China has the potential to become a leader. However, its status as the largest developing country in the regime shows that China has not chosen to be a hegemon. This choice opens an opportunity for the United States to take the lead on climate change issues again.